A treasure concealed [large type] - Peterson, Tracie (Peterson, Tracie. Sapphire brides, 2016)
1890s. Emily Carver is tired of following her gold-hunting father from one mining camp to another: she wants a home where she can put down roots. When she realizes she's losing her heart to the intriguing new man in their Montana camp, she is afraid that love will only result in disappointment and heartache. Caeden Thibault is a young geologist cataloging minerals indigenous to the state. He avoids romantic entanglements, fearing he might become like his abusive father. Will these two broken souls allow God to bring healing and hope to their hurting hearts?